Self-templated formation of hierarchical NiCo2O4 yolk-shell microspheres with enhanced electrochemical properties. (1st August 2017) - Leng, Jin; Wang, Zhixing; Li, Xinhai; Guo, Huajun; Li, Tao; Liang, Hongmei
Graphical abstract: Novel hierarchical NiCo2 O4 microspheres with a yolk-shell structure are successfully constructed via a two-step synthetic method combining a facile and scalable spray pyrolysis with a simple but powerful heat treatment process. The heat-treated temperatures can be adjusted to obtain different structured nickel-cobalt oxide microspheres. As LIB anode materials, The microspheres with yolk-shell structure exhibit significantly enhanced electrochemical performances. Highlights: Hierarchical yolk-shell NiCo2 O4 microspheres are successfully constructed. PVP is used as a functional template playing a vital role in structural design. The formation mechanism of yolk-shell structure is described in detail. The as-prepared microspheres show significantly enhanced electrochemical properties. Abstract: Novel hierarchical NiCo2 O4 microspheres with a yolk-shell structure are successfully constructed via a two-step synthetic method combining a facile and scalable spray pyrolysis with a simple but powerful heat treatment process. Polyvinylpyrrolidone (PVP) dissolved in precursor solution is used as a functional template playing a vital role in structural design. Hierarchical carbon combustion reactions of NiO@CoO@C precursor powder produce yolk-shell structure during the heat-treatment process. Heat-treated temperatures can be adjusted to obtain different structured nickel-cobalt oxide microspheres. As a potential anode material for Li-ion batteries, the hierarchical yolk-shell NiCo2 O4 microspheres exhibit a large reversible specific capacity of 984 mAh g −1 at a high current density of 1000 mA g −1 after 100 cycles, representing a high capacity retention of 98.2%. When operating at a current density of 5 A g −1, it delivers ultrafast charge-discharge performance, exhibiting a high capacity of 813 mAh g −1 . These excellent electrochemical properties very likely originate from characteristic yolk-shell structures, which provide buffer areas for the enormous volume expansion caused by Li-ion insertion/extraction and shorten the diffusion path of Li ions by increasing the contact area between the electrode and the electrolyte. This work may serve as a reference for the design of structurally novel functional materials in other advanced energy conversion and storage areas, such as supercapacitors, lithium–sulfur batteries, fuel cells, and Na-ion batteries.